Seven Finance and Trade Lessons from COVID-19 for Future Pandemics - Agarwal, Ruchir (IMF Working Papers; Working Paper, 2022)
Pandemics and epidemics pose risks to lives, societies, and economies, and their frequency is expected to increase as rising trade and increased human interaction with animals leads to the emergence of new diseases. The COVID-19 pandemic teaches us that we can and must be better prepared, with scope for much greater global coordination to address the financing, supply-chain, and trade barriers that amplified the pandemic's economic costs and contributed to the emergence of new variants. This paper draws seven early lessons from the COVID-19 pandemic that could inform future policy priorities and help shape a better global response to future crises.